1996
DOI: 10.1016/s0009-9236(96)90056-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of CYP2D6 polymorphism and quinidine on the disposition and antitussive effect of dextromethorphan in humans*

Abstract: The disposition of dextromethorphan was substantially influenced by CYP2D6 status. Capsaicin may not be an ideal agent in experimental cough studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
116
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(122 citation statements)
references
References 51 publications
3
116
0
Order By: Relevance
“…In contrast, the analysis of EM healthy subjects data from Kohler et al (1997) showed a very low correlation between the UMR in 8-h urine collection and in serum 1 h after DTM administration (r ϭ 0.19). Chladek et al (2000) found good correlation between UMR and 3-h plasma ratio (r ϭ 0.88), and Capon et al (1996) observed a similar correlation between the UMR and partial clearance of DTM to DT (r 2 ϭ 0.82). However, these studies included poor metabolizers in the analysis, and the correlations among EMs alone would be significantly lower.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In contrast, the analysis of EM healthy subjects data from Kohler et al (1997) showed a very low correlation between the UMR in 8-h urine collection and in serum 1 h after DTM administration (r ϭ 0.19). Chladek et al (2000) found good correlation between UMR and 3-h plasma ratio (r ϭ 0.88), and Capon et al (1996) observed a similar correlation between the UMR and partial clearance of DTM to DT (r 2 ϭ 0.82). However, these studies included poor metabolizers in the analysis, and the correlations among EMs alone would be significantly lower.…”
Section: Discussionmentioning
confidence: 67%
“…The formation of dextrorphan by CYP2D6 is responsible for approximately 97% of the oral clearance of dextromethorphan in EMs (Capon et al, 1996;Gorski et al, 2004). The dextromethorphan urinary metabolic ratio is a commonly used method for quantifying CYP2D6 activity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…DEX is extensively O-demethylated to dextrorphan by CYP2D6. The formation of DXO by CYP2D6 is responsible for approximately 97% of the oral clearance of DEX in EMs (Capon et al, 1996;Gorski et al, 2004). Dextrorphan then undergoes glucuronidation mostly by UGT2B7 (Lutz and Isoherranen, 2012).…”
Section: Downloaded Frommentioning
confidence: 99%
“…CL int,u,2D6 was estimated in Simcyp by simultaneously fitting observed plasma concentration-time profiles extracted from previous publications (Abdul Manap et al, 1999;Moghadamnia et al, 2003) (see Table 4). Optimization of CL int,u,2D6 was necessary to match predicted bioavailability (F a *F h *F g ;7%) to that reported (,5%) (Capon et al, 1996). CL r of DEX was assumed to approximate f u,p *GFR (see footnote to Table 4).…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation